Usage possibility of mannitol and soluble wheat fiber in low calorie gummy candies - Gok, Silan; Toker, Omer Said; Palabiyik, Ibrahim; Konar, Nevzat (ELSEVIER, 2020)
The aim of this study was to investigate effects of using different combinations of bulking agents (sucrose, mannitol and soluble wheat fiber) on the physico-chemical [moisture, water activity, soluble solid (SSC), color], texture and sensory properties of gummy candies formulated by maltitol syrup instead of glucose syrup. Experimental points of the study were determined by simplex lattice mixture design. Linear and quadratic models were determined for the effects on hedonic sensory properties and water activity, SSC, L *, chroma, various TPA (hardness, cohesiveness, springiness and resilience) parameters according to independent variables (p < 0.05). R-2 values of these models were determined between 0.579 and 0.999. With the increase of mannitol, negative changes were encountered in quality parameters other than brightness (L*). As a result of this study, it was determined that the solubility, crystallization behavior, hygroscopicity properties and sweetness level of alternative components should be taken into consideration in the selection of bulking sweeteners and agents in confectionery products. Also, it was determined that soluble wheat fiber can be a good alternative to reduce sucrose in gummy confectionery with fulfilling consumer demands and expectations.
Keywords: Confectionery; Sugar-free; Optimization; Mixture design; RHEOLOGICAL PROPERTIES; FLAVOR RELEASE; SUGARS; GELATIN; TEXTURE; ISOMALTULOSE; TEMPERATURE; FORMULATION; STABILITY; Food Science & Technology